Ulipristal acetate in uterine fibroids treatment - V V Korennaya; N M Podzolkova (IP Berlin A.V., 2013)
Ulipristal acetate is a selective progesterone receptor modulator, characterized by partial tissue-specific antiprogesteron effect, which is used in order to prepare uterine cancer patients for surgery. In the uterus it exerts an antiproliferative, anti-fibrotic and pro-apoptotic effects in relation to the uterine cells, which leads to downsizing of the nodes. Interaction of ulipristal with endometrium causes amenorrhea or bleeding decrease by the 10th day and reduces pain, which is important in symptomatic myoma. Its prescription at a dosage of 5 mg/day for 3 months reduces the volume of large fibroids, in average, by 45-50%. These results are comparable with the effect of agonists of gonadotropin-releasing hormone, but unlike them it's more easily transferred due to the lower likelihood of developing hypoestrogenism symptoms